Smart Solar Powered Plant Irrigation Water Sprinkler Agriculture Robot - Kamelia Wahid, Nur Kamelia; Jenal, Mahyuzie (Evolution in Electrical and Electronic Engineering, 2025)
This work intends to solve many problems like reducing wastage of water, harnessing natural energy and helping human do work more efficiently. As a result, it has taken the initiative to prevent water waste by developing a smart solar power plant irrigation water sprinkler plant. The project created an automated plant watering system and has distributed wireless network of sensor that are placed in mobile. An algorithm was developed with threshold values of sensor that was programmed into microcontroller-based gateway to control water quantity. Besides by integrating a solar panel provides a renewable energy source, reducing the reliance on external power supplies such as electricity or batteries. This makes the irrigation robot self-sustaining and capable of operating in remote or off-grid areas. As a result, the project is a success and able to provide sufficient water to the plants. Besides, water waste and energy consumption can be reduced since the project uses renewable energy so it is eco-friendly.